Property rights, collective action, and plant genetic resources - Eyzaguirre, Pablo B.; McCarthy, Nancy; Di Gregorio, Monica; Dennis, Evan (International Food Policy Research Institute, 2004)
Genetic resources are the genetic material in plants and animals that determine useful traits that people can conserve, characterize, evaluate, and use to meet their needs. These resources are not simply the genes encoded in DNA, but particular expressions of the genes that farmers, scientists, and plant breeders have recognized and selected. Research has estimated that the value of increases in crop yields derived from new genes and genetic modification since 1945 has amounted to about US$115 billion a year worldwide.